The significance of Controlling for a Company’s Strategic management - Mischenko, Volodymyr; Imeninnik, Anna; Partsyrna, Alla (University of Miskoc, 2011)
Controlling concepts are considered. Features of the concept of optimising the interests of separate proprietors of a joint-stock company are described. Peculiarities of using cost indices in strategic operation of business are reflected.
Keywords: market value; economic value added; market value added; profit; profitability; cash flow